2019
DOI: 10.1002/chem.201901956
|View full text |Cite
|
Sign up to set email alerts
|

2H Solid‐State NMR Spectroscopy Reveals the Dynamics of a Pyridine Probe Interacting with Coordinatively Unsaturated Metal Sites of MIL‐100(Al) Metal–Organic Frameworks

Abstract: Coordinatively unsaturated metal sites (CUS) play an important role in catalysis by metal‐organic frameworks (MOF). Being an intrinsic part of the framework the CUS take the role of acidic sites active in industrially relevant processes such as condensation or oxidation reactions. The key step of such reactions represents the coordination of the reagents to CUS. In MOFs the mechanism of the reagent interaction with CUS is poorly understood. Herein, we characterize the interaction of a widely used acidity probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The 31 P{ 1 H}, 13 C{ 1 H}, The standard single pulse (direct nuclear excitation) and/or cross polarization (CP) pulse sequences were applied for both 31 P and 13 C nuclei at time delays needed for the full spin-lattice relaxation. The contact times of 5 ms and 6 ms were adjusted for the 13 C and 31 P nuclei, respectively, to observe the regular proton-carbon and proton-phosphorus CP MAS NMR spectra. 31 P CSA values were obtained through the full data analysis of the NMR spectra with a standard Bruker program package exampled in Figure S1.…”
Section: Nmr Techniques and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 31 P{ 1 H}, 13 C{ 1 H}, The standard single pulse (direct nuclear excitation) and/or cross polarization (CP) pulse sequences were applied for both 31 P and 13 C nuclei at time delays needed for the full spin-lattice relaxation. The contact times of 5 ms and 6 ms were adjusted for the 13 C and 31 P nuclei, respectively, to observe the regular proton-carbon and proton-phosphorus CP MAS NMR spectra. 31 P CSA values were obtained through the full data analysis of the NMR spectra with a standard Bruker program package exampled in Figure S1.…”
Section: Nmr Techniques and Measurementsmentioning
confidence: 99%
“…[10,11] This technique is particularly useful for studies of intercalated phosphates, [12] where the behavior of deuterated guests can be well characterized by experiments on the 2 H nuclei. [13][14][15][16] Recently, by conducting 2 H and 31 P{ 1 H} solid-state MAS NMR experiments on a crystalline layered α-zirconium phosphate system, Zr (HPO 4 ) 2 Á0.35 D 2 O (1-D 2 O), including 31 P and 2 H T 1 measurements, [17] it has been revealed that there exists an unusual dynamic/bonding mode of the water, which is hydrogen bonded to the zirconium-coordinated oxygen and experiences a fast rotation (on the time scale of the NMR Larmor frequency) around this bond (Figure 1). At temperatures >253 K, the intercalated water unprecedentedly shows two spectrally distinguished deuterons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…rotational motions of pyridine on Al 3+ or Al-OH sites or the effects of adsorbates on the backbone. 122,123 This has been also successfully employed in different frameworks, [124][125][126] sometimes being able to discriminate between competing adsorbing molecules of very similar nature. 127 Thus, beyond the use of well-known basic probe molecules to study MOF acidity (e.g.…”
Section: Chemistry and Characterization Of Archetypal Metal-organic F...mentioning
confidence: 99%
“…Despite a notable number of the catalytic processes successfully tested for MOFs, [4b,7] the dynamics properties of the reactants involved remain unknown for the most of the cases. In fact, with a very few exceptions, [8] the experimental observation of the molecular mobility in MOFs was limited, so far, to relatively simple hydrocarbons [9] and small molecules such H 2 , [10] CO 2 [11] or water. [12] In addition, certain MOFs are capable of "breathing" by reversible change of the pore size upon guest molecules adsorption.…”
mentioning
confidence: 99%